The Effect of Net Interest Margin And Capital Adequacy Ratio on the Share Price of the Banking Sector Listed on the Indonesian Stock Exchange (Bei) in 2020 - 2023 - Raphael Frits Luhut Parulian Sihotang; Muhammad Syafi Romdony; Ario Purdianto; Erwin Budianto (Indonesian Journal of Business Analytics, 2025)
This study aims to identify and analyze the impact of Net Interest Margin and the effect of Capital Adequacy Ratio, as well as the combined effect of Net Interest Margin and Capital Adequacy Ratio on stock prices. A quantitative research method was employed for this study. The population consisted of 37 banking companies listed on the Indonesia Stock Exchange (IDX). The sampling method used was purposive sampling, selecting 20 companies that were consistent and met the sample selection criteria during the period from 2020 to 2023, resulting in 60 data points after the outlier removal process. The analytical model applied in this hypothesis includes descriptive statistics, classical assumption tests, regression equations, multiple linear regression analysis, partial tests, simultaneous tests, and coefficients of determination. The findings indicate that NIM does not have a significant effect on stock prices, CAR also does not significantly affect stock prices, and together, NIM and CAR do not have a significant impact on stock prices.